Effect of the dynamic curve type from the perifocal infiltration zone obtained by magnetic resonance imaging on prognosis in pelvic pathologies in women - T. A. Bergen; V. A. Fokin; G. E. Trufanov; A. V. Smagina; I. A. Soynov (Опухоли женской репродуктивной системы, 2020)
The aim of the study is to evaluate the role and prognostic significance of magnetic resonance imaging (MRI) perfusion methods in prognosis of disease course and outcome based on evaluation of the perifocal infiltration zone in pelvic disorders in women.Materials and methods. Retrospective analysis of pelvic MRI data obtained using MRI system with induced magnetic field of 1.5 T was performed. The study included 530 protocols of pelvic scans in women. Two equal groups (n = 265) of patients with oncological and nononcological pathologies of pelvic organs were formed; after application of propensity score matching, each group contained 165 patients. All examination protocols included dynamic contrast enhancement. The obtained data were statistically analyzed using the Stata 13 software.Results. In the study, types of dynamic curves obtained using dynamic contrast enhancement from the perifocal infiltration zone were analyzed. There was no data showing a correlation between the type of dynamic curve from the zone of perifocal changes and disease prognosis or possibility of differential diagnosis.Conclusions. Evaluation of the perifocal infiltration zone per MRI results with intravenous contrast does not affect prognostic accuracy of the method (p >0.05); contrast can be used only for differential diagnosis or evaluation of local advancement of the process.